Regulatory affairs on health Canada - R.Suthakaran; P. Sambasivarao; M. Ramesh; V.Padma; Raju.Manda (International Journal of Pharmacy and Analytical Research, 2022)
Regulatory affairs (RA), also called government affairs, is a profession within regulated industries, such as pharmaceuticals, medical devices, energy, banking, telecom etc. Regulatory affairs also has a very specific meaning within the healthcare industries ( pharmaceuticals, medical devices, biologics and functional foods). Regulatory affairs (medical affairs) professionals (aka regulatory professionals) usually have responsibility for the following general areas: Ensuring that their companies comply with all of the regulations and laws pertaining to their business. Working with federal, state, and local regulatory agencies and personnel on specific issues affecting their business. i.e. working with s uch agencies as the Food and Drug Administration or European Medicines Agency (pharmaceuticals and medical devices); The Department of Energy; or the Securities and Exchange Commission (banking).Advising their companies on the regulatory aspects and climate that would affect proposed activities. i.e. describing the "regulatory climate" around issues such as the promotion of prescription drugs and Sarbanes -Oxley compliance.